Diversification potential among the n-10 countries: an empirical investigation - Bhatia, P.; Kushwah, S.V. (International Journal of Accounting & Business Finance, 2023)
Emerging nations like Indonesia, South Korea, Bangladesh, Egypt, Mexico, Nigeria, Pakistan, Turkey, the Philippines, Iran and Vietnam have developing stock markets which may offer ample opportunities to investors for their portfolio returns. The emerging next ten countries (N-10) in the present paper have been explored for diversification opportunities for investors. The study has incorporated eight years’ (2013-2020) time series data for N-10 countries’ stock market indices. Portfolio diversification strategies between Pakistan and other markets have been indicated as per the findings of Granger causality, Johansen Cointegration techniques, VECM and Wald test. The unidirectional and bidirectional linkages analysis has shown fewer possibilities between Bangladesh and Egypt stock markets with diversification benefits. Thus, investors may utilise the findings of the study in planning their portfolio among these stock markets.
Keywords: N-10 countries; Diversification; Granger Causality; Cointegration; VECM; Stock markets